EFFECTS OF SOCIAL ISOLATION ON MENTAL HEALTH DURING COVID-19 IN THE CONTEXT OF AGEING - Koroļeva, Ilze; Sniķere, Sigita; Aleksandrovs, Aleksandrs; Reine, Ieva; Trapencieris, Mārcis; Ivanovs, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The COVID-19 pandemic brought significant changes to the usual rhythm of life. Reduced opportunities to meet with family members and friends in a situation of heightened stress leads to increased feelings of loneliness and social isolation, as well as increases the risk of mental health problems. The aim of this paper is to evaluate the effect of social contacts on the changes in psychoemotional states in the elderly population in Latvia during the crisis caused by the COVID-19 pandemic. The analysis draws upon quantitative data collected by the Survey of Health, Ageing and Retirement in Europe within Wave 8 in Latvia (n=1207). Measurements of the frequency of social contacts were used to construct social isolation indexes. Changes of psychoemotional state, characterized by sleeping problems, nervousness, frustration during the pandemic were included as dependent variables in multinomial logistic regression models that were run to identify the effect of social isolation on psychoemotional health in the context of other factors: age, gender, perceived health status, affluence and feelings of loneliness. The results show that in the group of those aged 50+, close to one-fifth of respondents experienced the effect of the COVID-19 crisis on their mental health. The link between reduced social contacts and changes in psychoemotional states proved to be statistically significant. In the group with the highest level of social isolation, irregularities in psychoemotional health are three times higher compared to other groups.